Life underneath the VCA umbrella: Perspectives from the US Uterus Transplant Consortium. Issue 5 (19th February 2021) - Johannesson, Liza; Wall, Anji; Tzakis, Andreas; Quintini, Cristiano; Richards, Elliott G.; O'Neill, Kathleen; Porrett, Paige M.; Testa, Giuliano
Abstract: The parallel emergence of uterus transplantation (UTx) and other transplantation innovations including face and hand transplantation led to the categorization of the uterus as a vascular composite allograft (VCA). With >60 transplants and >20 births worldwide, UTx is transitioning rapidly from a research endeavor to an effective treatment option for women with uterine factor infertility. While it originally made sense to group the innovations under one umbrella, it is time to revisit the designation of UTx as a VCA. We describe how UTx needs unique policy, procedural codes, insurance contracts, and educational initiatives. We contend that separating UTx from VCAs may become necessary in the future to avoid hindering the growth and regulation of this field. Abstract : The US Uterus Transplant Consortium reviews why uterus transplantation has grown up as a vascularized composite allograft and discusses how this categorization may shape future growth in the field.